Modelling within-team relative phase couplings using position derivatives in Australian rules football. Issue 4 (4th July 2017) - Spencer, Bartholomew; Robertson, Sam; Morgan, Stuart
ABSTRACT: Several approaches to the modelling of interpersonal movement coordination in sports, inspired by dynamical systems, have leveraged relative proximity to fixed ground points, such as the court midline to represent the phasic characteristics of movement in competition. While these approaches are useful in highly constrained sports such as tennis and squash, Australian football (AF) is played on a much larger playing area (approximately 150 m × 100 m) and is characterized by a 'rolling scrum' of interpersonal contests. Consequently, a different approach to modelling pairwise movement coordination is required. We propose a method that encodes interpersonal movement coordination using relative phase properties derived from angular velocity and acceleration. We demonstrate that these properties encode the level of temporal alignment of changes in running speed and direction between player pairs. This approach is illustrated using exemplar data from AF and explores net pairwise movement coordination within and between teams, and as a function of match duration.